2016
DOI: 10.1038/srep33879
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Non-depleted Serum Proteins from Bottlenose Dolphins Uncovers a High Vanin-1 Phenotype

Abstract: Targeted approaches have been widely used to help explain physiological adaptations, but few studies have used non-targeted omics approaches to explore differences between diving marine mammals and terrestrial mammals. A rank comparison of undepleted serum proteins from common bottlenose dolphins (Tursiops truncatus) and pooled normal human serum led to the discovery of 11 proteins that appeared exclusive to dolphin serum. Compared to the comprehensive human plasma proteome, 5 of 11 serum proteins had a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Plasma was assayed for total protein (Bio-Rad Protein Assay) and 5 μl was digested with trypsin (1:10 ratio enzyme to protein) for 18 h at 37 • C following following reduction and alkylation as we previously described [37]. Peptides were desalted using solid phase extraction cartridges (Strata-x, Phenomenex) and eluted sequentially in 25% acetonitrile/0.1% formic acid and 45% acetonitrile/0.1% formic acid.…”
Section: Proteomics and Data Processingmentioning
confidence: 99%
“…Plasma was assayed for total protein (Bio-Rad Protein Assay) and 5 μl was digested with trypsin (1:10 ratio enzyme to protein) for 18 h at 37 • C following following reduction and alkylation as we previously described [37]. Peptides were desalted using solid phase extraction cartridges (Strata-x, Phenomenex) and eluted sequentially in 25% acetonitrile/0.1% formic acid and 45% acetonitrile/0.1% formic acid.…”
Section: Proteomics and Data Processingmentioning
confidence: 99%
“…However, only 206 proteins were identified from the cerebrospinal fluid of 11 California sea lions 22 . Conversely, two previous studies of plasma samples from bottlenose dolphins (T ursiops truncates ) only identified 58 and 196 unique proteins, respectively 23 , 24 . Thus, those results suggested that the complexity of the protein compositions of marine mammals varies between different tissues and species.…”
Section: Discussionmentioning
confidence: 75%
“…The present study performed a preliminary analysis of the differences in the protein profiles obtained from the blood sera collected at different time points from male rats exposed to low concentrations of MTBE using the polyacrylamide gel electrophoresis technique. SDS-PAGE has been previously and successfully used to detect a novel, blood-based prostate cancer marker [22,23]. Carbonic anhydrases (CAs) have been studied for over 90 years [24].…”
Section: Discussionmentioning
confidence: 99%